General Practitioners Using Complementary and Alternative Medicine Differ From General Practitioners Using Conventional Medicine in Their View of the Risks of Electromagnetic Fields - Bernd Kowall; Jürgen Breckenkamp; Gabriele Berg-Beckhoff (SAGE Publishing, 2015)
Objective: General practitioners (GPs) play a key role in consulting patients worried about health effects of electromagnetic fields (EMF). We compared GPs using conventional medicine (COM) with GPs using complementary and alternative medicine (CAM) concerning their perception of EMF risks. Moreover, we assessed whether the kind of alternative medicine has an influence on the results. Methods: A total of 2795 GPs drawn randomly from lists of German GPs were sent an either long or short self-administered postal questionnaire on EMF-related topics. Adjusted logistic regression models were fitted to assess the association of an education in alternative medicine with various aspects of perceiving EMF risks. Results: Concern about EMF, misconceptions about EMF, and distrust toward scientific organizations are more prevalent in CAM-GPs. CAM-GPs more often falsely believed that mobile phone use can lead to head warming of more than 1°C (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.5-3.3), more often distrusted the Federal Office for Radiation Protection (OR = 2.2, 95% CI = 1.4-3.6), were more often concerned about mobile phone base stations (OR = 2.4, 95% CI = 1.6-3.6), more often attributed own health complaints to EMF (OR = 3.2, 95% CI = 1.8-5.6), and more often reported at least 1 EMF consultation (OR = 2.5, 95% CI = 1.6-3.9). GPs using homeopathy perceived EMF as more risky than GPs using acupuncture or naturopathic treatment. Conclusion: Concern about common EMF sources is highly prevalent among German GPs. CAM-GPs perceive stronger associations between EMF and health problems than COM-GPs. There is a need for evidence-based information about EMF risks for GPs and particularly for CAM-GPs. This is the precondition that GPs can inform patients about EMF and health in line with current scientific knowledge.